Dynamic interface mechanical behavior between geogrid and marine silica sand considering temperature effects - Kong, Xiangshen; Zhang, Liman; Xu, Kaiwei; Liu, Yanqi; Cui, Peng; Pu, Xiaogang (Frontiers in Earth Science, 2025)
To comprehensively examine the dynamic shear characteristics of the marine silica sand–geogrid interface under representative marine environmental conditions, a series of cyclic direct shear tests with controlled temperature were carried out using a custom-designed experimental apparatus. The interface between marine silica sand (particle size 0.075–2 mm) and a biaxial geogrid was examined across a wide temperature range (−5°C–80°C) and under varying normal stresses (50, 150, and 250 kPa). The coupled effects of temperature and normal stress on the interfacial cyclic shear response were systematically analyzed. The results demonstrate that the interfacial shear behavior is markedly influenced by the combined effects of temperature and normal stress. Under a normal stress of 50 kPa, the peak shear stress increases progressively with the number of loading cycles, indicating shear hardening behavior. At normal stress of 150 kPa, the peak shear stress gradually stabilizes, indicating a movement toward mechanical equilibrium. In contrast, at a normal stress of 250 kPa, the shear stress increases during the initial cycles but then declines, demonstrating a shift toward shear softening behavior. Additionally, as the temperature increases from −5 °C to 20 °C, both the interfacial strength and stiffness show noticeable improvement. However, further heating to 80 °C results in a significant deterioration of these mechanical properties. Notably, the interface behavior under 250 kPa exhibits the highest sensitivity to temperature variation. Furthermore, the maximum dynamic shear stiffness increases with temperature up to 20 °C and subsequently declines, whereas the damping ratio is highest during the initial cycle and gradually stabilizes with continued cyclic loading. The results emphasize the significant and interconnected impacts of temperature and normal stress on the dynamic behavior of the interface between marine silica sand and geogrid. These findings provide valuable insights for the design, improvement, and long-term assessment of geosynthetic-reinforced systems in marine engineering applications.